(1324) الفوارق الاقليميه في مصر وطرق قياسها Regional differences in Egypt and methods of measuring them - السيد محمد كيلاني ، سيد محمد عبد المقصود (معهد التخطيط القومي, 2026)
تناقش الدراسة مشكلة "الازدواجية الإقليمية" في مصر، حيث تتركز التنمية في أقاليم حضرية محددة بينما تعاني بقية الأقاليم من التخلف، مما يؤدي لظهور فوارق ديموجرافية واقتصادية واجتماعية حادة ، وتوضح الدراسة أن تركز الاستثمارات والخدمات في القاهرة والإسكندرية حوّلهما إلى مراكز جذب قوية للسكان ورؤوس الأموال، في حين ظلت المحافظات الريفية (خاصة في مصر العليا) مناطق طاردة تعاني من البطالة المقنعة وتدني مستويات المعيشة، مما عمّق الفجوة التنموية وأدى إلى تزايد الهجرة الداخلية وتكدس السكان في مساحات ضيقة من الحيز المكاني، استخدمت الدراسة أدوات إحصائية مثل "معامل التباين" و"معامل التركز" لقياس هذه الفوارق، وكشفت النتائج أن حدة التفاوت في مصر تتجاوز بمراحل نظيرتها في دول متقدمة ونامية أخرى، كما طرحت الدراسة نموذجاً رياضياً لحساب "البعد الزمني" اللازم للحاق الأقاليم المتخلفة بالأقاليم المتقدمة، وأظهرت النتائج أن بعض المستويات المتأخرة قد تحتاج لعشرات السنين للوصول للمستوى الحالي للقاهرة والإسكندرية في ظل المعدلات الحالية (pp. 22, 27). وتخلص الدراسة إلى ضرورة تبني سياسة تخطيطية تعيد توزيع الاستثمارات جغرافياً وتفجر طاقات النمو الكامنة في المحافظات الأقل حظاً لضمان توازن الهيكل المكاني القومي. The study discusses the problem of "regional duality" in Egypt, where development is concentrated in specific urban regions while the rest of the regions suffer from underdevelopment, leading to the emergence of sharp demographic, economic and social disparities. The study explains that the concentration of investments and services in Cairo and Alexandria has turned them into strong centers of attraction for the population and capital, while the rural governorates (especially in Upper Egypt) have remained areas of exclusion suffering from disguised unemployment and low standards of living, which has deepened the development gap and led to an increase in internal migration and the overcrowding of the population in narrow areas of space. The study used statistical tools such as the "coefficient of variance" and the "concentration coefficient" to measure these disparities, and the results revealed that the severity of the disparity in Egypt far exceeds that of other developed and developing countries. The study also presented a mathematical model to calculate the "time distance" required for the underdeveloped regions to catch up with the developed regions, and the results showed that some of the lagging levels may need decades to reach the current level of Cairo and Alexandria under current rates (pp. 22, 27). The study concludes that it is necessary to adopt a planning policy that redistributes investments geographically and unleashes the latent growth potential in the less fortunate governorates to ensure a balanced national spatial structure.